The Influence of Smoking Habits on the Incidence of Prostate Carcinoma - Sinaga, Lisa Kristiani; Hendrianto, Hendrianto; Rahimi, Armon (Newinera Publisher, 2025)
Adenocarcinoma is the most common type of prostate cancer, caused by the abnormal growth of prostate gland cells. Prostate cancer ranks as the second most common cancer in men globally and is the fifth leading cause of cancer-related deaths. Smoking is identified as a significant risk factor for prostate cancer due to carcinogens such as cadmium and polycyclic aromatic hydrocarbons, which can damage DNA and increase oxidative stress. This study used a cross-sectional design with 92 patients at Dr. Pirngadi Hospital in Medan to analyze the relationship between smoking habits and the incidence of prostate carcinoma. The results show a significant association between smoking and an increased risk of prostate cancer, with a p-value of < 0.001. The study also found a significant effect of the Brinkman Index, which measures the intensity of smoking habits, on the degree of differentiation of prostate carcinoma (p < 0.001). These findings highlight the importance of early detection and public education on the dangers of smoking in preventing prostate cancer.